WHEAT GENETIC RESOURCES IN RUSSIA: CURRENT STATUS AND PRE-BREEDING - O. P. Mitrofanova (Вавиловский журнал генетики и селекции)
One of the largest world wheat collections maintained in a living state at the N.I. Vavilov Research Institute of Plant Industry, St. Petersburg, is described, and studies conducted with the collection are reviewed. The history of pre-breeding studies and results of genetic diversity evaluation of wheat samples by means of DNA markers is surveyed.